Hepatitis B Surface Antigen and Viral DNA Detection and Prevalence in Nige-ria - Desmond, Abazuh Uchenna; Tola, Ohiengbomwan Onaiwu; Isaac, Adeolu; Mercy, Yusuf (UI Scholars Hub, 2020)
Hepatitis B infection is a major public health issue with a high mortality rate. It is caused by hepatitis B virus (HBV), a small incomplete hepadnavirus with several open reading frames (ORF). High mutation rates of the HBV ORFs due to the virus’ replicating strategy are associated with the development and emergence of mutant strains, which may result in occult infections that are undetectable by conventional diagnostic assays. In this study, we first investigated the presence and prevalence of hepatitis B surface antigen (HBsAg) and HBV DNA among 204 patients visiting the specialist hospital in Osogbo, Nigeria, by using the Acumen diagnostic test strip kit and PCR amplification of the surface antigen gene. Then, we compared the positive results detected by both assays. The mean age of the participants was 30.5 years. Twenty-two (10.78%) cases were positive in the HBsAg test, and 69 (33.82%) cases were positive for HBV DNA. Fifty-four false-negatives (26.47%) and four false-positives (1.96%) were detected by HBsAg. The rapid diagnostic test kit is less sensitivity and has lower detection capability compared with the PCR-based assay, which indicates the presence of mutant HBV strain(s). The results of this work demonstrate that HBsAg is endemic in Nigeria and that HBV DNA is highly prevalent among the population. Our findings highlight the need for immediate action to prevent the further spread of infection.